2010
DOI: 10.1111/j.1556-4029.2010.01580.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Contraction During Electro‐muscular Incapacitation: A Comparison Between Square‐wave Pulses and the TASER® X26 Electronic Control Device*

Abstract: Electronic control devices (including the Advanced TASER(®) X26 model produced by TASER International) incapacitate individuals by causing muscle contractions. To provide information relevant to development of future potential devices, effects of monophasic square waves with different parameters were compared with those of the X26 electronic control device, using two animal models (frogs and swine). Pulse power, electrical pulse charge, pulse duration, and pulse repetition frequency affected muscle contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It has also been noted that the most energy‐efficient pulse duration for stimulation is in the range of 100 μs . In a previous study , we showed there was no difference in the electrical pulse charge required, between the square waveform and the commercial CEW waveform when applied at comparable repetition rates and at similar pulse durations, to cause approximately the same muscle contraction response (in terms of the strength–duration curve). Among four different types of waveforms ([a] square, [b] Gaussian, [c] increasing exponential, and [d] decreasing exponential pulses), the square pulse required the least energy to elicit equivalent force responses of limbs of the swine Sus scrofa .…”
mentioning
confidence: 62%
“…It has also been noted that the most energy‐efficient pulse duration for stimulation is in the range of 100 μs . In a previous study , we showed there was no difference in the electrical pulse charge required, between the square waveform and the commercial CEW waveform when applied at comparable repetition rates and at similar pulse durations, to cause approximately the same muscle contraction response (in terms of the strength–duration curve). Among four different types of waveforms ([a] square, [b] Gaussian, [c] increasing exponential, and [d] decreasing exponential pulses), the square pulse required the least energy to elicit equivalent force responses of limbs of the swine Sus scrofa .…”
mentioning
confidence: 62%
“…The detailed shape of a CEW waveform may not be important in terms of generating electromuscular incapacitation . Although some in the general public may presume that “electrocution” occurs in any death temporally related to use of a CEW, repeated applications of the device do not result in a “cumulative dose” of electricity per se .…”
Section: Physiological Factors During Short‐duration Vs Longer‐duratmentioning
confidence: 99%
“…Overseas, Jeffrey, D. H. [6] analyzed the conductive currents of CEW in the human body and the potentially physiological effects after electrocution. James, A. C. [7] compared the difference in interference of electromyographic signal (EMG) and control of muscle under the effected of square wave pulses and the narrow pulses generated from Taser x26 CEW. Sebastian, N. K. [8] studied the effect of electrocution on heart and skeletal muscle through the biological and human experiment.…”
Section: Introductionmentioning
confidence: 99%